Hubungan Durasi Kerja dengan Kejadian Forward Head Posture pada Pegawai Pelayanan Publik di DIY - Galih Siwi Cahyaningrum; Asyhara Naela Arifin; Wika Yuniarwati (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Public service employees encounter significant work demands, which include prolonged hours and sedentary positions, especially while sitting and utilizing computers for longer durations. These conditions increase the risk of musculoskeletal problems, including Forward Head Posture (FHP). FHP is defined by an anterior head position and may result in neck discomfort, functional limitations, and reduced occupational productivity. This study aims to determine the relationship between work duration (years of service, duration of computer use, and daily work hours) and the prevalence of mild and severe Forward Head Posture among public service employees in the Special Region of Yogyakarta (DIY). This was a quantitative study employing crossectional design. The sample was taken using the total sampling technique on public service employees with a total of 85 respondents. Forward Head Posture was assessed using the Craniovertebral Angle (CVA) utilizing the ON Protractor application, while data on work duration was collected by interviews. The Spearman Rank correlation test was employed for data analysis. The findings indicated that most respondents exhibited mild to severe levels of Forward Head Posture. Statistical analyses revealed a strong correlation between work duration and the prevalence of Forward Head Posture (p < 0.05). The extended period of work and computer usage correlates with an increased severity of Forward Head Posture (FHP). A significant correlation exists between work length and the prevalence of mild and severe Forward Head Posture among public service employees in the Special Region of Yogyakarta. The implementation of ergonomic practices and physiotherapy interventions is essential as both promotive and preventative strategies to mitigate the risk of musculoskeletal problems.